2006
DOI: 10.1644/06-mamm-f-038r2.1
|View full text |Cite
|
Sign up to set email alerts
|

Speciation in Mammals and the Genetic Species Concept

Abstract: We define a genetic species as a group of genetically compatible interbreeding natural populations that is genetically isolated from other such groups. This focus on genetic isolation rather than reproductive isolation distinguishes the Genetic Species Concept from the Biological Species Concept. Recognition of species that are genetically isolated (but not reproductively isolated) results in an enhanced understanding of biodiversity and the nature of speciation as well as speciation-based issues and evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

69
432
12
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 636 publications
(526 citation statements)
references
References 100 publications
69
432
12
13
Order By: Relevance
“…The average genetic distances between other sister species of Cryptotis (sensu Guevara and Cervantes 2013) range from 2.0% to 6.8% (Table 3; e.g., C. magnus and C. phillipsii, 6.8%; C. mexicanus and C. obscurus, 5.1%; C. goldmani and C. peregrinus, 2.0%). Small (, 5%) genetic distances are known for other closely related species of mammals that had been recognized on the basis of morphology before use of molecular approaches (see Baker and Bradley 2006). The genetic distances support our morphological result in allying the Lacandona shrew most closely with the C. nigrescens species group rather than either the C. mexicanus or C. parvus groups.…”
Section: Resultssupporting
confidence: 71%
“…The average genetic distances between other sister species of Cryptotis (sensu Guevara and Cervantes 2013) range from 2.0% to 6.8% (Table 3; e.g., C. magnus and C. phillipsii, 6.8%; C. mexicanus and C. obscurus, 5.1%; C. goldmani and C. peregrinus, 2.0%). Small (, 5%) genetic distances are known for other closely related species of mammals that had been recognized on the basis of morphology before use of molecular approaches (see Baker and Bradley 2006). The genetic distances support our morphological result in allying the Lacandona shrew most closely with the C. nigrescens species group rather than either the C. mexicanus or C. parvus groups.…”
Section: Resultssupporting
confidence: 71%
“…Furthermore, our maximum estimate of the TMRCA among these species is ∼3.5 Mya, a value younger than the hypothesized rate of hybrid inviability for mammals (18,41). The patterns of differential rates of reproductive isolation in allopatry described above are compatible with theoretical models of speciation (18,42,43). Theoretical treatments of hybrid speciation have shown that speciation is likely to occur faster when the chromosomal differences between the parental taxa were low and the hybrids were common in a given population (44).…”
Section: Discussionsupporting
confidence: 74%
“…We recognize that in some kinds of animals and many kinds of plants, the grouping of ''genus'' and ''family'' may not reflect monophyletic groups; thus, we confine our analysis to mammals, in which these ranks typically do reflect monophyly and aggregate similar evolutionary distances (27)(28)(29). We focus on mammals, because there is little disagreement that most genera are monophyletic and do in fact reflect a real evolutionary grouping, although we of course recognize some may object to even using the term ''genus'' in view of current phylogenetic practice.…”
mentioning
confidence: 99%
“…Most mammal species in North America are significantly older than 130,000 years. In fact, the mean divergence between North American sister species (within genera) is at least an order of magnitude older (27,28,34). Thus, we predict that the intrinsic traits (e.g., trait-based controls on geographic range) that define range size in these animals evolved before the LP glacial-interglacial cycles and, accordingly, we anticipate that the relative range sizes will remain fairly constant, simply because North American mammalian species have witnessed repeated glacial-interglacial cycles in their lifespan (as many as 18 cycles; ref.…”
mentioning
confidence: 99%